Application of psychodynamic model in the assessment and management of psychogenic voice disorder: a case report - Sruthi, K. Vinod; Rahul, Akhila (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The psychological state is considered to contribute to the overall well-being of an individual. Disequilibrium due to psychological reasons such as anxiety, stress, depression, or other psychological conditions may affect voice production entirely or partially, significantly affecting the person’s occupational, social, and emotional well-being. The present study discusses a sudden onset of aphonia in a 37-year-old female without an underlying physiological illness. The study illustrates the importance of interpreting the voice problem in the patient considering the influence of the individual's psychological, physiological, physical, emotional, and social health by applying the psychodynamic model.